Spatial and temporal trends of number of deaths attributable to ambient PM2.5 in the Korea - Han, Changwoo; Kim, Soontae; Lim, Youn Hee; Bae, Hyun Joo; Hong, Yun Chul (Journal of Korean Medical Science, 2018)
Background: We aimed to evaluate the spatial and temporal trends of the health burden attributable to particulate matter less than 2.5 μm in diameter (PM2.5) in the metropolitan cities and provinces of the Korea. Methods: We used modeled PM2.5 concentration data for the basic administrative levels, comprising the cities and the provinces of Korea, the corresponding annual population census data for each level, and the age and cause specific mortality data. We applied cause-specific integrated exposure-response functions to calculate the premature mortality attributable to ambient PM2.5 for four disease end points (ischemic heart disease [IHD], chronic obstructive pulmonary disease [COPD], lung cancer [LC], and cerebrovascular disease [stroke]) for the year 2015. Moreover, the temporal trends of the health burden from 2006 to 2015 were assessed. Results: The annual average PM2.5 concentration for Korea was 24.4 μg/m3, and 11,924 premature deaths were attributable to PM2.5 exposure in 2015. By simulating the reduction in the annual mean values of PM2.5 to 10 μg/m3, about 8,539 premature deaths were preventable. There was spatial variation in mortality burden attributable to PM2.5 across the sub-national regions of Korea. In particular, the high burden was concentrated at Seoul and Gyeonggi province due to the high population density. However, decreasing trends were noted for most of the metropolitan cities and provinces of Korea since 2006. Conclusion: Our findings show that further actions to improve air quality in Korea would substantially improve the health burden due to particulate matter.
Keywords: Air Pollutants; Air Pollution; Cities; Environmental Exposure; Particulate Matter; Republic of Korea; Health Burden; Korea; Mortality; Particulate Matter